Rankings of Canadian Universities: Pitfalls in Interpretation - Page, Stewart (Canadian Journal of Higher Education, 1995)
A critical perspective is presented in regard to rankings of Canadian universi- ties by Maclean's magazine, November 11, 1993. Some brief comparisons are also made in regard to the 1992 rankings and data. Several pitfalls in the rank- ing procedures, and the results of some correlational analyses of the ranking data, are outlined. A brief summary of comments and some implications are presented, bearing on the wider issue of 'public' university accountability and also on the practical issue of students' choice of universities.